Distinct germ-line genetic mutation patterns correlate with reproductive outcomes in ICSI patients: a pilot study - Ting Jiang; Yan Wang; Wandai Wu; Qianru Yang; Sixian Wu; Xueguang Zhang; Wenming Xu (Frontiers in Genetics)
BackgroundInfertility affects approximately 15% of couples worldwide, with male factors accounting for nearly 50% of cases. Intracytoplasmic sperm injection (ICSI) has become the standard treatment for male factor infertility, but outcomes vary significantly among couples. While conventional genetic testing using blood samples is common in reproductive medicine, the genetic composition of sperm may differ significantly from somatic cells due to mosaicism and de novo mutations during spermatogenesis.MethodsWe collected semen samples from 11 couples with varying ICSI outcomes: successful clinical pregnancy (n = 6), implantation failure (n = 3), and early pregnancy loss (n = 2). Sperm DNA was extracted using magnetic-activated cell separation and whole-exome sequencing was performed. The sequencing data were aligned to the GRCh37/hg19 reference genome and analyzed for potentially pathogenic mutations. Semen analysis and karyotype were also evaluated.ResultsSemen analysis showed no significant differences between groups except for sperm morphology. Whole-exome sequencing identified distinct mutation patterns between groups. Mutations in USP9X, SPAG6 and ADGRG2 were observed in the clinical pregnancy group. Implantation failure and pregnancy loss were associated with mutations in genes involved in embryo adhesion, immune regulation, and genomic stability, including MAGEC1, MUC4 and SERPINA2.ConclusionThis pilot study suggests that direct sperm exome sequencing may reveal genetic variants associated with different ICSI outcomes. While our findings require validation in larger cohorts, they generate hypotheses about sperm-specific factors that might influence post-fertilization developmental events and pregnancy outcomes.